A Comparative Review of Communication Differences Between Chinese and American Families in Child Upbringing - Chensihan Xiao (Journal of Linguistics and Communication Studies, 2023)
This discussion examines the influence of communication differences on various aspects of child development, including cognition, language acquisition, emotional regulation, self-esteem, and social relationships with peers. It also explores the significance of cross-cultural perspectives on communication and child upbringing, highlighting the importance of understanding and appreciating the strengths and limitations of diverse communication styles. The role of cultural sensitivity and understanding is emphasized, along with strategies to promote effective communication within multicultural families. By recognizing and adapting to communication differences, parents and caregivers can create a supportive and inclusive environment that fosters healthy child development and positive family dynamics.